Vận dụng mô hình nghiên cứu bài học vào dạy học ở tiểu học và trung học cơ sở: Kết quả nghiên cứu và bài học kinh nghiệm (Viện KHGD Việt Nam, 2020)
Lesson study has become widely common in school across Japan and many other countries. This model has been tried out, however the scale is still limited. In 2007-09 Can Tho University and Michigan State University has conducted a study on applying the lesson study in primary and lower secondary education in the difficult area and got good results. This article presents some of the findings and related lessons.